2022
DOI: 10.3390/ijerph19148541
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Perceived Discrimination and Mental Health of Wage Workers with Disabilities: Findings from the Panel Survey of Employment for the Disabled 2016–2018

Abstract: Despite efforts to integrate society, persons with disabilities (PWD) still experience considerable discrimination. Therefore, this study examined the association between experiences of discrimination and stress/depressive symptoms in wage working PWD. This study used data from the Panel Survey of Employment for the Disabled 2016–2018 in South Korea. This study included 1566 wage working PWD aged 15–64. The dependent variable was stress and depressive symptoms, and the independent variable was the experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A common focus lies on misconceptions and stigmatization directed towards disabled employees [ 31 , 35 , 36 , 47 , 65 , 71 73 , 78 , 91 , 98 , 100 , 104 , 105 ]. Moreover, the studies underscore instances of unjust treatment faced by disabled employees, ranging from insulting and bullying [ 36 , 41 , 44 , 58 , 62 , 73 , 82 , 119 ] to incidents of harassment and violence [ 95 , 115 , 122 , 124 ]. Additionally, some studies address the phenomenon of coworker jealousy when disabled employees are granted work accommodations [ 45 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…A common focus lies on misconceptions and stigmatization directed towards disabled employees [ 31 , 35 , 36 , 47 , 65 , 71 73 , 78 , 91 , 98 , 100 , 104 , 105 ]. Moreover, the studies underscore instances of unjust treatment faced by disabled employees, ranging from insulting and bullying [ 36 , 41 , 44 , 58 , 62 , 73 , 82 , 119 ] to incidents of harassment and violence [ 95 , 115 , 122 , 124 ]. Additionally, some studies address the phenomenon of coworker jealousy when disabled employees are granted work accommodations [ 45 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings from a 2014 census of the Canadian federal public service revealed that disability was significantly associated with increased odds of workplace harassment and discrimination [68]. Discriminatory phenomena and WV also emerged from the Panel Survey of Employment for the Disabled 2016-2018 in South Korea [69], as well as from the Household, Income, and Labour Dynamics in Australia ("HILDA") survey [70]. The same happens with ageing: older nurses are often the targets of incivility in the workplace.…”
Section: Discussionmentioning
confidence: 99%